2010
DOI: 10.1002/jctb.2491
|View full text |Cite
|
Sign up to set email alerts
|

Production of biodiesel from wet activated sludge

Abstract: BACKGROUND: The production of biodiesel from activated sludge obtained from Tuscaloosa, AL was optimized based on the yield of fatty acid methyl esters (FAMEs) using an in situ transesterification process. An orthogonal central composite response surface design was considered to investigate the main and interaction effects of temperature, methanol to sludge ratio, and catalyst concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 26 publications
1
36
1
Order By: Relevance
“…A series of initial studies investigated lipid extraction and direct transesterification of raw sewage sludges containing adsorbed oils and lipid-containing microbial cells resulting into oil yields of 7-10 wt % and biodiesel yields of up to 2-5 wt %. [20][21][22][23] In the most recent study aimed at increasing the oil and biodiesel yields from sewage sludge, activated sludge microorganisms were cultivated in aerobic bioreactors operating at initial C:N ratio 70:1 and 60 g/L glucose loading to elicit oleaginous behavior among the constituents of this natural microbial consortium. Sludge biomass with increased lipid content and biodiesel yield of around 17.5 6 3.9 wt % and 10.2 6 2.0 wt %, respectively were generated-significantly higher than those obtained from raw sewage activated sludge.…”
Section: Introductionmentioning
confidence: 99%
“…A series of initial studies investigated lipid extraction and direct transesterification of raw sewage sludges containing adsorbed oils and lipid-containing microbial cells resulting into oil yields of 7-10 wt % and biodiesel yields of up to 2-5 wt %. [20][21][22][23] In the most recent study aimed at increasing the oil and biodiesel yields from sewage sludge, activated sludge microorganisms were cultivated in aerobic bioreactors operating at initial C:N ratio 70:1 and 60 g/L glucose loading to elicit oleaginous behavior among the constituents of this natural microbial consortium. Sludge biomass with increased lipid content and biodiesel yield of around 17.5 6 3.9 wt % and 10.2 6 2.0 wt %, respectively were generated-significantly higher than those obtained from raw sewage activated sludge.…”
Section: Introductionmentioning
confidence: 99%
“…The major problem of using animal fat for biodiesel production in the basic catalytic process is high water content and free fatty acids. Industrial wastes such as activated sludge were also reported as feedstock for biodiesel production [27].…”
Section: Introductionmentioning
confidence: 99%
“…As municipal sewage sludge is a waste, formed during the treatment of wastewater, it is a possible alternative source of lipids for the production of biodiesel, consequently lowering the wastewater treatment plant (WWTP) operation costs [15][16][17][18][19][20]. Research has shown that the lipids contained in sewage sludge are a potential feedstock for biodiesel mainly and comprised of fatty acids predominantly in the range of C10 to C18, which are excellent for the production of biodiesel [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As municipal sewage sludge is a waste, formed during the treatment of wastewater, it is a possible alternative source of lipids for the production of biodiesel, consequently lowering the wastewater treatment plant (WWTP) operation costs [15][16][17][18][19][20]. However, there are still different technical and economical constraints required to be solved before scaling-up into industrial scale can be reached.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation